The Failed History of Quarantines, and Its Implications for Public Health - Sanjeev Sabhlok; Paul Frijters; Gigi Foster; Jay Bhattacharya; Ari R. Joffe (Institute of Labor Economics (IZA), 2024)
This paper reviews the history of the practice of quarantines, rediscovering the 19th century 'Sanitarian' movement in Britain that sprang from a recognition that quarantines had failed to stop the spread of diseases and were not cost-effective. To our knowledge, the key figure among the Sanitarians was Charles Maclean, who conducted the first cost-benefit analysis of quarantines. MacLean heavily influenced, among others, Southwood Smith and Edwin Chadwick, who, together with Jeremy Bentham, championed reforms that form part of the Public Health Act of 1848, which led to the primacy of sanitation efforts (such as pressurised water supply, sewage management, and garbage collection and safe disposal) in public health policy in the UK and elsewhere. Maclean convinced the Sanitarians that quarantines were not grounded in health science but instead formed part of the business model of a public health bureaucracy uninterested in public health and which was prepared to falsify and ignore data to survive. Arguably, the same can be said today with the modern version of quarantines being the Covid lockdowns of 2020-2021. We sketch a few preliminary institutional options for freeing public health efforts from bureaucratic expansion and mission drift and tethering them more robustly to the public interest.
Keywords: I18; H00; N30; 330; public health; quarantines; social distancing; cost-benefit; excess deaths; health bureaucracy; mission drift